AMEE Education Guide no. 28: The development and role of departments of medical education - Davis, M.H.; Karunathilake, I.M.; Harden, Ronald M. (My University, 2005)
SUMMARY A department of medical education is becoming an essential requirement for a medical school. This publication is intended for those wishing to establish or develop a medical education department. It may also prove useful to teachers in medicine by providing information on how such a department can support their activities. This will vary with the local context but the principles are generalizable. Medical education departments are established in response to increased public expectations relating to healthcare, societal trends towards increased accountability, educational developments, increased interest in what to teach and how to educate doctors and the need to train more doctors. The functions of a department of medical education include research, teaching, service provision and career development of the staff. The scope of its activities includes undergraduate and postgraduate education, continuing professional development and continuing medical education. These activities may be extended to other healthcare professions. Flexibility is the key to staffing a department of medical education. Various contractual arrangements, affiliations and support from non-affiliated personnel are needed to provide a multi-professional team with a range of expertise. The precise structure of the department will depend on the individual institution. The name of the department may suggest its position within the university structure. The director provides academic leadership for the department and his/her responsibilities include promotion of staff collaboration, fostering career development of the staff and establishing local, regional and international links. Financial support may come from external funding agencies, government or university sources. Some departments of medical education are financially self-supporting. The department should be closely integrated with the medical school. Support for the department from the dean is an essential factor for sustainability. Several case studies of medical education departments throughout the world are included as examples of the different roles and functions of a department of medical education.